PENGARUH SUPLEMENTASI TEPUNG KROKOT (Portulaca oleracea) TERHADAP SEL DARAH MERAH, HEMOGLOBIN, DAN PACKED CELL VOLUME PADA KAMBING JAWARANDU (Capra aegagrus hircus) - Arif Irawan; Madi Hartono; Agung Kusuma Wijaya; Sri Suharyati (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the best dose of purslane flour on red blood cells, hemoglobin, and packed cell volume in Jawarandu Goats. This research was conducted in February-March 2021 at the Rambon Asri Cattle Group, Rejo Asri Village, Seputih Raman District, Central Lampung Regency, Lampung Province. Examination of red blood cells, hemoglobin, and packed cell volume was carried out at the Veterinary Center of Lampung Province. The experiment used was a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were basal ration (P0), basal ration with 5% purslane flour supplementation (P1), basal ration with 10% purslane flour supplementation (P2), and basal ration with 15% purslane flour supplementation (P3). The data obtained were analyzed using analysis of variance with a significance level of 5% and continued with orthogonal polynomials. The results showed that purslane flour supplementation had no significant effect (P>0.05) on total erythrocytes and hemoglobin, but had a significant effect (P<0.05) on the volume of packed cells of Jawarandu Goat. The optimum dose of purslane flour supplementation on red blood cells, hemoglobin, and hematocrit were 3.01% Kg/BK ration, 2.17% Kg/BK ration, and 3.16% Kg/BK ration, respectively. Keywords: Hemoglobin, Jawarandu goat, Packed cell volume, Red blood cells, Purslane flour